2022
DOI: 10.3389/fcvm.2021.780123
|View full text |Cite
|
Sign up to set email alerts
|

Circular Network of Coregulated Sphingolipids Dictates Chronic Hypoxia Damage in Patients With Tetralogy of Fallot

Abstract: Background: Tetralogy of Fallot (TOF) is the most common cyanotic heart disease. However, the association of cardiac metabolic reprogramming changes and underlying molecular mechanisms in TOF-related chronic myocardial hypoxia damage are still unclear.Methods: In this study, we combined microarray transcriptomics analysis with liquid chromatography tandem-mass spectrometry (LC–MS/MS) spectrum metabolomics analysis to establish the metabolic reprogramming that occurs in response to chronic hypoxia damage. Two G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Orthogonal partial least squares-discriminant analysis (OPLS-DA) and principal component analysis (PCA) were carried out using R ( 19 ). Metabolites with differential expression between two groups were identified by the variable importance in prediction (VIP) ≥ 1 ( 20 ) and | log2FC| ≥ 1 ( 4 , 21 ). From the OPLS-DA results, we extracted VIPs, and we conducted permutation test (200 permutations) to avoid over-fitting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthogonal partial least squares-discriminant analysis (OPLS-DA) and principal component analysis (PCA) were carried out using R ( 19 ). Metabolites with differential expression between two groups were identified by the variable importance in prediction (VIP) ≥ 1 ( 20 ) and | log2FC| ≥ 1 ( 4 , 21 ). From the OPLS-DA results, we extracted VIPs, and we conducted permutation test (200 permutations) to avoid over-fitting.…”
Section: Methodsmentioning
confidence: 99%
“…TOF is considered as a prototype CHD ( 2 ), which affects 3 out of 10,000 live births ( 3 ). In addition, it is the most common cause of CHD ( 4 ), which represents that 7–10% of CHD occurs in 0.5/1,000 live births ( 5 ). TOF is mainly due to the abnormal development of the arterial cone, leading to pulmonary artery stenosis, ventricular septal defect, aortic span, and finally leading to right ventricular hypertrophy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combining transcriptomics and metabolomics analysis, by means of liquid chromatography coupled with mass spectrometry, on right atrial specimens in TOF patients, showed a downregulation of sphingolipids. This may reflect the chronic hypoxia experienced in many patients with TOF [ 20 ].…”
Section: Specific Congenital Heart Diseasesmentioning
confidence: 99%